1992
DOI: 10.2190/2nhn-nuy7-q88u-cdjh
|View full text |Cite
|
Sign up to set email alerts
|

Women as Home Caregivers: Gender Portrayal in OTC Drug Commercials

Abstract: Concern has long been expressed over possible adverse effects of television advertising of over-the-counter (OTC) medicines. This study investigated a sample of prime time network television ads to determine how gender portrayals differed in drug and non-drug commercials. Findings indicated that women were significantly more likely than men to appear as characters in drug ads than in ads for other products, and that they are frequently portrayed in these commercials as experts on home medical care, often as mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In a study on medication use among adults, it was shown that prescription drugs were used more commonly among women than men, 11 and, thus, women might have been more likely to have medications to share with others. Women might act as "family doctors," as they are often portrayed in drug commercials, 12 making them more comfortable in sharing prescriptions or prescribing them for others. Top reasons for use of prescription medications among adults in the U.S. include hypertension, headache, heart, allergy, and pain (not otherwise specified); we found that allergy and pain medications were the most frequently shared medications.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on medication use among adults, it was shown that prescription drugs were used more commonly among women than men, 11 and, thus, women might have been more likely to have medications to share with others. Women might act as "family doctors," as they are often portrayed in drug commercials, 12 making them more comfortable in sharing prescriptions or prescribing them for others. Top reasons for use of prescription medications among adults in the U.S. include hypertension, headache, heart, allergy, and pain (not otherwise specified); we found that allergy and pain medications were the most frequently shared medications.…”
Section: Discussionmentioning
confidence: 99%
“…First, consistent with current research on prime-time advertising, all national commercials were coded including repeated ads (Craig, 1992). Local commercials, political advertisements, trailers for television shows, movies, and sports events were excluded (Bartsch, Burnetts, Diller, & Rankin-Williams, 2000;Wilkes & Valencia, 1989).…”
Section: Units Of Analysesmentioning
confidence: 99%
“…Some recent studies of gender-role portrayals in US advertising have been devoted to one type of advertising (Craig, 1992;Hansen & Osborne, 1995;Leppard et al, 1993). It is found that gender bias against women also exists, for example, in drug advertising.…”
Section: Literature Reviewmentioning
confidence: 99%